2014
DOI: 10.1016/j.aller.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and resistin in overweight patients with and without asthma

Abstract: Background: Excess body mass increases the risk of development of asthmatic symptoms and their severity and decreases the treatment effectiveness. One of the hypotheses explaining the link between the two diseases concerns the adipokines, hormones produced by adipose tissue with a proinflammatory character. The aim of this study was to compare the levels of the adipokines (leptin and resistin) between overweight asthmatic patients, asthmatic patients with normal weight and overweight patients without asthma. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
15
0
3
Order By: Relevance
“…18,23 Importantly, BALB/c mice are prone to develop allergic-like Th2 immune responses, 24 being more adequate for asthma models. In addition, clinical studies have demonstrated that obesity worsens asthma symptoms in women; 10,12,25 therefore the present study was developed in a female model. We have shown that mice fed an HFD not only gained more weight than mice fed a standard diet ( Fig.…”
Section: Hfd Efficiently Induces Obesitymentioning
confidence: 99%
“…18,23 Importantly, BALB/c mice are prone to develop allergic-like Th2 immune responses, 24 being more adequate for asthma models. In addition, clinical studies have demonstrated that obesity worsens asthma symptoms in women; 10,12,25 therefore the present study was developed in a female model. We have shown that mice fed an HFD not only gained more weight than mice fed a standard diet ( Fig.…”
Section: Hfd Efficiently Induces Obesitymentioning
confidence: 99%
“…Adipokines regulate energy homeostasis through hunger and satiety control (96,97) . Some adipokines such as leptin or resistin are produced in excess in obesity (98) , while others, such as adiponectin and ghrelin are reduced. This imbalance promotes pro-inflammatory responses and leads to inflammation (99)(100)(101) .…”
Section: Possible Linksmentioning
confidence: 99%
“…Surely, some part of the link can be explained by overestimation due to fat mass on the thoracic chest mimicking asthma symptoms (65) ; part of the weight increase may also be due to medication or decreased activity caused by exercise-induced wheezing attacks, resulting in reverse causation (61) . There is no doubt that the endocrine role of adipose tissue (adipokines) is a strong physiological link and very plausibly could be a mechanism in causing a chain of disruption leading to inflammation and narrowing of airways (98,(105)(106)(107) . Despite existing evidence indicating that adipokines may be a plausible link between obesity and asthma, clinical studies bring inconclusive results.…”
Section: Possible Linksmentioning
confidence: 99%
“…Although the levels of both adipokines were higher in patients with overweight and asthma as compared to healthy overweight subjects, these differences were not significant. Patients with and without asthma and overweight (BMI ≥ 25) and with an increased waist circumference showed a higher level of leptin [17].…”
Section: Reviewmentioning
confidence: 99%